Análise dos fatores de risco de infecções em corrente sanguínea em pacientes renais crônicos em uso de cateter venoso em hemodiálise - Prado, Bruna Linhares (2020)
Chronic Kidney Disease (DRC) is characterized by the progressive loss of kidney function, being associated with a reduction of life expectancy in patients affected. In the more advanced stages of CKD, there is a need for costly treatments, such as hemodialysis and kidney transplantation. Were analyzed the risk factors that cause bloodstream infections in chronic renal patients using a central venous catheter undergoing hemodialysis at a hospital in Sobral, CE. Forty-four patients participated in the study, 70.5% were men and 29.5% were women. Patients were divided according to age group into two groups: 24-50 years and over 50 years old. Of the total, 52.3% were older than 50 years, and 47.7% were up to 50 years old.The most prevalent social classes were D, C2 and C1, respectively with 38.6%, 28.5% and 18.2%. When were analyzed according to the absence of infection, social class C1 and C2 were equal, with 32.4%. As for the predominance of infection, class D was the highest, with 60%. Related to the Khan index, the total number of patients in relevance was the moderate index with 45.5%. The main etiologies of chronic kidney disease were diabetes (31.8%), followed by indeterminate ones (29.5 %%), followed by hypertension (27.3%) and polycystic kidney disease (6.8%). Obstructive nephropathy was the most relevant etiology in the presence of infection, being a risk factor for this, in relation to the statistical analysis of this variable, it was significant (p <0.05). The HD time was divided between up to and above 6 months of treatment. Of the patients analyzed, 54.5% were within 6 months of treatment. In the dialysis unit (75%) and in the emergency room (13.6%), catheter implantation procedures were the most frequently performed environments, respectively. All patients who had hyperemia (50%) also had chills (80%), only 3 did not. With these signs and symptoms the most prescribed treatment was Vancomycin (80%), it is noteworthy that 20% used Amikacin associated with Vancomycin. In this study, risk factors were found that involved the etiology of the disease, the length of time the catheter remained, a reason that culminated in the exchange of the device and complications during the hemodialysis session. The results obtained provide important data for the hemodialysis service, also for instituting infection prevention and control measures